2021
DOI: 10.1212/wnl.0000000000012806
|View full text |Cite
|
Sign up to set email alerts
|

Reflection on the Past, Present, and Future of Thrombolytic Therapy for Acute Ischemic Stroke

Abstract: More than 25 years have passed since the US Food and Drug Administration approved IV recombinant tissue plasminogen activator (alteplase) for the treatment of acute ischemic stroke. This landmark decision brought a previously untreatable disease into a new therapeutic landscape, providing inspiration for clinicians and hope to patients. Since that time, the use of alteplase in the clinical setting has become standard of care, continually improving with quality measures such as door-to-needle times and other me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…and continuously optimized. 5 No such widely adopted time-based metrics currently exist for ICH (Figure 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…and continuously optimized. 5 No such widely adopted time-based metrics currently exist for ICH (Figure 1).…”
mentioning
confidence: 99%
“…Quality metrics including door-to-needle and door-to-groin puncture time are measured, reported, and continuously optimized. 5 No such widely adopted time-based metrics currently exist for ICH (Figure 1).…”
mentioning
confidence: 99%
“…With endovascular therapy advances, multiple studies are investigating whether thrombolytic therapy can be bypassed in patients with LVO, where initial presentation is at thrombectomy or comprehensive stroke centers, in order to be treated with primary MT, as the case of acute myocardial infarction. To date, these studies have failed to provide any shared results and not one of these studies has reported an overall noninferiority when compared to combined treatment [180]. Moreover, the use of advanced neuroimaging techniques could allow the evaluation of collateral circulation status before and after revascularization strategies, to more consciously guide the management of AIS patients and reduce the rate of “futile recanalization,” as well as the design of clinical trials on interventions having collateral circulation as target to obtain a better clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…EVT has been a critical advance in the management of LVO, but there is a continued role for thrombolysis in a subset of patients. Demel et al 28 investigate the opportunity for novel or adjunctive IV pharmacologic agents to achieve reperfusion. Specifically, safer and more efficacious drugs may allow for faster delivery of therapy (particularly when EVT is not immediately available) as well as facilitate recanalization (particularly of more distal occlusions).…”
Section: Treatments: Lytics and Neuroprotectionmentioning
confidence: 99%